Alternating Hemiplegia of Childhood: Report of Two Cases - Fatema, Kanij; Rahman, Md Mizanur; Akter, Shaheen; Begum, Suraiya; Islam, Md Tanvir (Journal of Enam Medical College, 2018)
Alternating hemiplegia of childhood (AHC) is a rare disorder which presents before 18 months of age characterized by repeated attacks of hemiplegia involving either side of the body, paroxysmal disturbances,developmental delay and learning disability. The cause of AHC remains largely unknown and treatment evidence is less available. AHC is unreported in Bangladeshi literature. We report two cases of AHC. Our first case is a 16-month-old girl who presented with hemiplegia in alternate side for four episodes. She also had abnormal body movement and irritability during awakening. Every episode subsided spontaneously after 2 to 5 days. All investigations were normal except iron deficiency anemia. She was treated with flunarizine. Our second case, a 7 year and 10 month-old boy presented with recurrent alternate hemiplegia since 3½ years of age with epilepsy. His attacks were precipitated in high temperature. His EEG was abnormal. He was treated with multiple antiepileptic drugs and flunarizine. These are first two cases reported from Bangladesh. AHC remains undiagnosed in many cases. So a detailed history and diagnostic evaluation is very important for early counseling and treatment. J Enam Med Col 2018; 8(1): 46-49